Prudential Banking Principle Implementation In Murabahah Financing On PT. Sumut Sharia Bank Branch Padangsidimpuan - Lestari, sry; Renfiana, Lilis; Arianti, Fitri (Journal of Islamic Financial Technology, 2022)
Based on the data on the number of murabahah financing customers of PT. Bank Sumut Padangsidimpuan Sharia Branch As of 31 December 2016-2019. In 2017 it decreased by 5.15 percent, in 2018 it experienced an increase of 5.36 percent, and in 2019 it experienced an increase of 6.01 percent. Therefore researchers are interested in researching the implementation of prudential banking principles in murabaha financing. The purpose of this study was to determine the application of the prudential banking principle in murabahah financing at the Padangsimpuan Branch of Bank Sumut Syariah. The theory used in this study is the theory of applying, the theory of the prudential principle, the theory of murabaha, the theory of murabaha financing. This research is descriptive qualitative with data collection techniques using interviews, observation, and documentation, while the data sources used are primary data and secondary data. From the results of this study it can be concluded that the implementation of prudential banking principle is the 5C principle of character, capacity, capital, economic conditions, collateral. collateral). The implementation of the prudential banking principle for murabahah financing has implemented the 5C principle. It can be seen that in 2018 and 2019 there has been an increase.